PENGARUH DIVERSIFIKASI PENDAPATAN TERHADAP RISIKO DAN KINERJA BANK - , Aryanti S. Sianipar ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Portfolio theory suggests that by diversification investors can obtain benefits of decreasing risk and increasing return. This theory motivates banks managers to shift their activities from lending activities to non-interest activities, such as fee generating and trading activities. These activities not only affect the performance but also the risk of the bank. The strategy of diversification is implemented by large banks and small banks. Large banks gain more benefits of decreasing risk compared with small banks because they have more proportions of non-interest income and better resources. This study examines the effect of bank revenue diversification on risk and performance of listed banks in Indonesia Stock Exchange over the period 2004-2012. Using panel data with measures of risk based on market data and accounting data, this study finds diversification decreases bank unsystematic and total risk. Banks gain benefits of decreasing unsystematic and total risk by increasing their fee income. This study finds no evidence of increasing market value from non-interest income although non-interest income affects banks profitability positively and cost inefficiency negatively. There is no difference of diversification effect on risk between large banks and small banks. Large banks only enjoy lower market beta compared to small banks when the proportion of non-interest income is high. Higher proportion of trading income leads to lower market beta.